2016
DOI: 10.1631/jzus.b1600229
|View full text |Cite
|
Sign up to set email alerts
|

Influence of low protein diets on gene expression of digestive enzymes and hormone secretion in the gastrointestinal tract of young weaned piglets

Abstract: Abstract:To investigate dietary protein level effects on digestive mechanisms, weaned piglets were fed for 45 d with diets containing 20%, 17%, or 14% crude protein (CP) supplemented to meet requirements for essential amino acids. This article describes the influence of dietary protein on gastrointestinal hormones and expression of an array of digestive enzymes in the gastrointestinal tract and pancreas. Results indicated that there were no significant differences in expression of enzymes involved in carbohydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 36 publications
3
20
0
Order By: Relevance
“…There was no significant difference (P > 0.05) between the 17% and 20% CP diet groups (Figure 3). This result is consistent with previous results showing that a protein-restricted diet can affect the expression of chymotrypsin, aminopeptidase, amylase, and carboxypeptidase [50,60]; however, it is not consistent with previous results indicating that a proteinrestricted diet cannot affect the expression of pepsinogen and trypsinogen in pigs [4,50,60]. Therefore, in the present study, the 17% CP-restricted diet can increase the expression of genes encoding pepsinogen in the stomach but induced a trend toward higher mRNA levels of trypsinogen, chymotrypsin, CPA, and α-amylase than those in other groups, although there were no significant differences.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…There was no significant difference (P > 0.05) between the 17% and 20% CP diet groups (Figure 3). This result is consistent with previous results showing that a protein-restricted diet can affect the expression of chymotrypsin, aminopeptidase, amylase, and carboxypeptidase [50,60]; however, it is not consistent with previous results indicating that a proteinrestricted diet cannot affect the expression of pepsinogen and trypsinogen in pigs [4,50,60]. Therefore, in the present study, the 17% CP-restricted diet can increase the expression of genes encoding pepsinogen in the stomach but induced a trend toward higher mRNA levels of trypsinogen, chymotrypsin, CPA, and α-amylase than those in other groups, although there were no significant differences.…”
Section: Discussionsupporting
confidence: 94%
“…The nutrient sensing of CaSR is expressed in a number of tissues and is involved in calcium homeostasis and the regulation of a variety of cellular processes, including proliferation, differentiation, expression, ion channel function and hormone secretion, as well as fluid absorption [23]. CCK can stimulate gallbladder contraction and pancreatic growth [50], and L-phenylalanine L-tryptophan can stimulate the release of CCK from isolated CCK cells [51]. The diets AAs with higher affinity for CaSR are the aromatic AAs L-tryptophan, L-phenylalanine, L-tyrosine and L-histidine, where basic and branch-chain AAs are the least effective [52].…”
Section: Discussionmentioning
confidence: 99%
“…The intestinal sucrase and lactase activities had increased expression in piglets fed dietary high carbohydrate‐fed piglets, which could suggest increased carbohydrate metabolism (Tian et al, ). However, this does not seem to be overtly utilized for improved body weight gain.…”
Section: Discussionmentioning
confidence: 99%
“…Animals and management were described in Tian et al (2016). In this experiment, we just select small intestinal samples of young pigs from two groups: pigs fed with 20% and 17% CP based on NRC (2012) recommendations (Supplemental Table 1).…”
Section: Animals and Dietmentioning
confidence: 99%
“…Li et al (2017) also found that there were no differences on growth performance of piglets between 17% CP 20% CP group. Our previous research (Tian et al, 2016) showed that 17% CP diet was in favor of digestion and absorption of the nutrient in the intestine of piglets, and the mRNA abundance of many kinds proteases in piglets fed diets containing 17% CP tended to be higher than those of piglets fed diets containing 20% CP, which implied that reducing dietary CP content and supplementing with free AA meeting specific requirements improves the nitrogen utilization efficiency without affecting the growth performance of piglets. Proteomics profiles analysis result (Ma et al, 2015) showed that compared with 20% CP group, some signal pathways such as protein digestion and absorption pathway, PI3K-Akt signaling pathway, focal adhesion pathway and coagulation cascades pathway were up-regulated in 17% CP group.…”
Section: Introductionmentioning
confidence: 95%